Application of lightning performance analysis for a tropical climate country - Baharuddin M.Z.; Abiding I.Z.; Hashim A.H.; Hussein H.; Chin Y.E.; Mohamad A.M. (IEEE Computer Society, 2023)
A tropical climate country experience high lightning related activities. This can be represented in terms of the keraunic level which lies within the region of 100 to 150 thunderstorm days per year. For a utility company, the high keraunic level would contribute to high possibility of power interruptions. These outages would ultimately lead to loss of revenue and reduced network reliability. These lightning related interruptions may be in terms of direct strikes to the line. Apart from that a consequent back flashover may result from an indirect lightning strike near the vicinity of the line. The aggregate of the direct and indirect lightning strikes would contribute to the overall lightning performance of the line This paper outlines the application of a lightning performance analysis tool based upon the IEEE Std 1410-2004 conditioned for a tropical climate country. Results and analysis indicates factors that would affect the lightning performance of the line. The contributing factors found from these analyses would be dependent upon the environment at which the line is located, eg. presence of tall objects which ultimately acts as a lightning shield would improve the lightning performance whereas if the lines are located in an open field, the probability of lightning strikes would be high. Based upon these factors, a list of possible mitigating actions is presented in improving the lightning performance of the une. 2006 IEEE.